2013
DOI: 10.1093/ajh/hps071
|View full text |Cite
|
Sign up to set email alerts
|

Association of Television Viewing Time With Central Hemodynamic Parameters and the Radial Augmentation Index in Adults

Abstract: Television viewing time was directly correlated with PAIx75 in an adult population. This correlation was maintained even after adjustment for physical activity, age, sex, and other cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…Edwards et al [10] found physical activity to be associated to PWV and to the central augmentation index (CAIx) in adolescents and young adults. RecioRodriguez et al [11] published the time spent watching television to be directly correlated to the peripheral augmentation index (PAIx) in adults. On the other hand, Madura et al [12] showed that the changes in arterial stiffness parameters due to aerobic exercise are reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Edwards et al [10] found physical activity to be associated to PWV and to the central augmentation index (CAIx) in adolescents and young adults. RecioRodriguez et al [11] published the time spent watching television to be directly correlated to the peripheral augmentation index (PAIx) in adults. On the other hand, Madura et al [12] showed that the changes in arterial stiffness parameters due to aerobic exercise are reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that sedentary time is associated with lipoprotein lipase activity, a protein involved in plasma triglyceride catabolism, HDL cholesterol, and other metabolic risk factors (24). A study on vascular aging found that increasing television viewing time directly correlated with an increase in peripheral augmentation index, a marker of arterial stiffness (25). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, less physical activity or prolonged sedentarism was associated to greater aging of the vascular system [10,68]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the results are even more relevant on combining the time spent seated (6 hours a day) with low physical activity (< 24.5 METS/hours/week), yielding a relative risk (RR) of 1.94 (95% confidence interval (95% CI): 1.70-2.20) for women and 1.48 (95% CI: 1.33-1.65) for males, as opposed to those who spend less time seated and have greater activity [9]. The EVIDENT study has also found increased arterial stiffness to be related to the number of hours spent watching television [10]. On the other hand, physical activity shows an inverse correlation to the concentrations of fibrinogen [11].…”
Section: Introductionmentioning
confidence: 99%